FACING THE UNSEEN: A CRITICAL EXAMINATION OF MENTAL HEALTH CHALLENGES IN THE NURSING PROFESSION - Ahlam Ali Shargan Algamdi, Ghaitha Muhammed Haider, Sharifah Ali Shargan Algamdi, Hamdah Naji Mohd, Hasnah Sayyah Al-Zubaidi, Halima Saeed Essa Asiri Midwafery, Nasser Muhammad Alkhreem, Hadiah Mubarak Ali (Chelonian Research Foundation, 2023)
In the demanding landscape of healthcare, nurses emerge as pivotal figures, navigating the complexities of patient care with unwavering commitment. However, beneath their resilient exteriors lies a concerning vulnerability to mental health challenges, often overshadowed by the physical demands of their profession. This article, "Facing the Unseen: A Critical Examination of Mental Health Challenges in the Nursing Profession," delves into the multifaceted psychological struggles encountered by nurses. Through a critical lens, it explores the prevalence and types of mental health issues, including stress, anxiety, depression, and PTSD, that pervade the nursing community. The investigation extends to identifying the intrinsic and extrinsic factors contributing to these challenges, such as high-stress environments, emotional labor, and insufficient support systems. By comparing these struggles with those in other high-stress professions, the article highlights the unique position of nursing. It discusses the profound implications on personal wellbeing, professional performance, and patient care quality, underscoring the urgent need for comprehensive support mechanisms. The article concludes with actionable recommendations, advocating for systemic changes encompassing individual coping strategies, institutional support, and policy advocacy, aimed at fostering a healthier work environment and ensuring the sustenance of the nursing profession's core values. Keywords: Mental Health Challenges, Nursing Profession, Stress and Anxiety in Nursing, Emotional Labor, Professional Support Systems, Healthcare Work Environment, Coping Strategies in Nursing, Systemic Changes in Healthcare.